Current studies on human papillomavirus in Saudi Arabia - Fatimah Saeed Alhamlan; Ahmed A Al-Qahtani; Mohammed N Al-Ahdal (Journal of Infection in Developing Countries)
Human papillomavirus (HPV) infection is a significant etiological factor and an important prognosticator in cervical cancer. Indeed, researchers worldwide have confirmed these roles for high-risk HVPs in over 70% of cervical cancer cases. According to the World Health Organization, approximately 561,200 new cancer cases (5.2% of all new cancers) are attributed to HPV infection. Over 120 types of HPV are classified further as either low-risk HPV (LR-HPV) or high-risk HPV (HR-HPV) based on their oncological potential of transforming cells. The LR-HPV types cause benign hyperproliferative lesions (i.e. genital warts) while the HR-HPV types are strongly associated with premalignant and malignant cervical lesions. Data on the prevalence of HPV, survival of infected patients, and mortality rate are scarce in Saudi Arabia. The unsubstantiated assumption of a low prevalence of HPV in Saudi Arabia has contributed to limiting HPV research in this conservative country. Therefore, the goal of this review is to shed light on the current HPV research being conducted and the prevalence of HPV in Saudi Arabia.